The Role of Smartphone Applications as English Learning Tool among Chinese University Students (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to explore the impact of smartphone applications on Chinese non-English majors’ out-of-classEnglish listening learning. The qualitative research method was adopted in this study. Four participants who attended the semistructuredinterviews and five online diaries were selected to provide data for the research. The results demonstrate that th eutilization of smartphone apps can indeed have a positive influence on Chinese non-English majors' out-of-class Englishlistening learning, and change their listening learning styles to a great extent. Fragmented learning time and informal learningplace were widely accepted by students due to the flexibility and portability of smartphone apps, which create more learningopportunities for them and in turn lengthens their learning time. Rich, authentic, high-quality, and up-to-date listeningmaterials, English proficiency tests, and the function of recommendation offered by smartphone apps all provide a greatconvenience for students. However, this technology is not yet mature and can be further developed by ameliorating somenegative factors, such as interference from other functions and applications of smartphones, small screens and reflected light,and lack of guidance and feedback.